An Introduction to K-Pop and BTS - Cho, Joanne Miyang. author. aut Link
IX, 177 p.
Keywords: This Palgrave Pivot examines a key area of the Korean Wave or Hallyu, which stands for the global popularity of South Korean popular culture that started in the 1990s. While K-dramas (Korean dramas) have found many viewers throughout Asian countries and some Western countries in recent years, K-pop (Korean popular music) has had broader appeal not only to Asian audiences, but also American (North and South), European, and Middle-Eastern audiences. This book’s unique contribution is to provide a concise and succinct analysis of K-pop from transcultural perspectives through its most famous example, BTS. The first chapter contextualizes K-pop within the Korean Wave movement. The second and third chapters provide a history of K-Pop, spanning from Seo Taiji and Boys in the early 1990s to the present (including BTS and Blackpink), and presents K-pop as a glocalized phenomenon. The fourth, fifth, and sixth chapters critically examine the most prominent band in the K-pop world, BTS, and the unique connections to their transnational fandom called ARMY. Joanne Miyang Cho is Professor at William Paterson University of New Jersey, USA. Tessa C. Lee is Associate Professor of German Studies at Wheaton College, USA.